2021
DOI: 10.3390/educsci11120762
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of University Missions on Entrepreneurial Initiative across Multiple Entrepreneurial Ecosystems: Evidence from Europe

Abstract: Entrepreneurial universities are a significant element of entrepreneurial ecosystems and aspire to foster entrepreneurial initiative through their “third mission”. However, while entrepreneurial ecosystems are scrutinized using a contextual approach to detect differences and similarities and how they affect entrepreneurship, little is known about how entrepreneurial universities impact entrepreneurial initiatives in general, considering multiple environments. Drawing on entrepreneurial university and entrepren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
0
8
0
3
Order By: Relevance
“…Women were overrepresented in the sample, as well as professors, while academics in health sciences, and arts, are underrepresented. This may have some impact of the results as former studies (Pita et al, 2021; Calvo et al, 2019; Lam, 2011) have shown that males are more active in innovation and entrepreneurial actives than females, and academics in health and life sciences are more active in commercialisation of research than academics in social sciences and humanities (Powers, 2003; Stuart and Ding, 2006). Younger academics are also more likely to participate in TM activities than professors as already noted.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Women were overrepresented in the sample, as well as professors, while academics in health sciences, and arts, are underrepresented. This may have some impact of the results as former studies (Pita et al, 2021; Calvo et al, 2019; Lam, 2011) have shown that males are more active in innovation and entrepreneurial actives than females, and academics in health and life sciences are more active in commercialisation of research than academics in social sciences and humanities (Powers, 2003; Stuart and Ding, 2006). Younger academics are also more likely to participate in TM activities than professors as already noted.…”
Section: Discussionmentioning
confidence: 94%
“…Male academics have been found to be more involved in entrepreneurship and collaboration with industry than their female counterparts (Pita et al, 2021;Calvo et al, 2019;Lam, 2011) and have higher entrepreneurial intentions (Iakovleva and Adkins, 2022). Reasons for this are higher proportion of male academics in innovation and technology-driven fields in science, technology, engineering, and mathematic fields (STEM), as well as a higher participation in networks outside of academia (e.g.…”
Section: Motivations For Participating In Tm and Collaborationmentioning
confidence: 99%
“…Por otra parte, se propone una definición de empresario a partir de la actitud emprendedora, que significa tomar acciones humanas creativas para construir algo de valor a partir de una decisión con certidumbre o incertidumbre (Hidalgo, 2014); y toma una posición crítica frente al emprendimiento y las instituciones que se dedican a su fomento, expresando que, lo más importante es crear una mentalidad emprendedora basada en competencias y habilidades en la toma de decisiones y gerenciales (Uribe-Toril et al, 2019). Esta expresión, por ejemplo, es el eje de la mayor parte de los esfuerzos de la Unión Europea para promover la educación emprendedora en los centros de educación superior (Pita et al, 2021), sindo importante porque orientan al desarrollo emprendedor en un sentido más amplio que el de la creación de una empresa.…”
Section: ¿Qué Se Entiende Por Emprendimiento?unclassified
“…Junto a ello, el desarrollo de competencias hacia el establecimiento de una cultura emprendedora debe ser acompañado por políticas claras de incentivos y promoción de los agentes del desarrollo y sus actores (Okolie y Ogbaekirigwe, 2014; Ukah y Atah, 2021), puesto que se hace indispensable que todos los actores de la sociedad identifiquen su papel dentro de la cadena productiva, convirtiendo al emprendimiento, más que en un proyecto, en un eje programático dentro de la planeación estratégica de los espacios locales, del cual se desprenden lineamientos tan fuertes como la transformación de la educación (Prasad et al, 2018;Pita et al, 2021).…”
Section: Competencias En Los Emprendedoresunclassified
See 1 more Smart Citation